PENINGKATAN PEMAHAMAN SUMBER DAYA MANUSIA DAN IMPLEMENTASI REGULASI DALAM PUSAT PEMBELAJARAN KELUARGA (PUSPAGA) KOTA BAUBAU - Ode Dedi Abdullah, La (Jurnal Abdimas Adpi Sosial dan Humaniora, 2020)
Increasing understanding of human resources about the regulation of the family learning center (PUSPAGA) in Baubau City is very much needed, this is because it can support and foster / increase understanding of human resources on the importance of a family learning center so that a city with quality families can be realized. This paper identifies problems, among others: there are still many people who are not fully aware of the existence of a family learning center, how to participate in the membership of family learning centers as well as many people who do not fully know and implement legal values ​​/ rules that contain prohibitions and orders not to commit Domestic Violence. This paper aims to increase understanding of : 1) Human Resources Knowledge, 2) ways to participate in family learning center memberships and 3) understand and implement legal values ​​/ rules which contain prohibitions and orders not to commit domestic violence. The method used is socialization, counseling and discussion. Increased understanding of human resources, knowing how to participate in membership and implementing regulations in a good family learning center will certainly encourage the growth of a harmonious family that matches the expectations of the family itself and is in accordance with government programs